The learning and teaching of mathematical modelling - Niss, Mogens; Blum, W. 1945- (IMPACT: Interweaving mathematics pedagogy and content for teaching, 2020)
"This book takes stock of the state of affairs of the teaching and learning of mathematical modelling with regard to research, development and practice. It provides a conceptual framework for mathematical modelling in mathematics education at all education levels, as well as the background and resources for teachers to acquire the knowledge and competencies that will allow them to successfully include modelling in their teaching, with an emphasis on the secondary school level. Equally, mathematics teacher educators, mathematics education researchers and developers will benefit from this book"--